Über Coleophora robustella Fuchs, Coleophora ciconiella Herrich-Schäffer und Coleophora silenella Herrich-Schäffer (Lepidoptera: Coleophoridae). - Patzak, Helmut (Contributions to Entomology = Beiträge zur Entomologie, 1969)
Studies of authentic material provided that Coleophora robustella Fuchs is not identical with Coleophora onosmella Brahm but very closely related with Coleophora silenella Herrich-Schäffer. Coleophora robustella Fuchs largely agrees in its appearance and male genitals with the sparse confirmed material of Coleophora ciconiella Herrich-Schäffer and is very probably identical with this species. The proof depends on finding a definite female of Coleophora ciconiella Herrich-Schäffer. A species occurring in Austria and Poland and east of these countries, which in appearance and biology resembles Coleophora silenella Herrich-Schäffer and which Toll regarded as ciconiella, is probably a different species not yet described.